Modelling the time on unemployment insurance benefits - Govert E. Bijwaard (Institute for the Study of Labor (IZA), 2007)
A duration model based on the time on Unemployment Insurance (UI) benefits instead of a model based on the time till re-employment is more relevant from a cost-benefit perspective. The contribution of this paper is to extend the standard (mixed) Proportional Hazard model to account for an upper bound on the duration. We use a modified mover-stayer model to this end and discuss the interpretation of the parameters. In an empirical application we compare the method with the standard analysis of unemployment duration. We also derive the expected UI-benefit costs implied by the model for some typical unemployed individuals.
Keywords: 330; Arbeitslosigkeit; Dauer; Arbeitslosenversicherung; Kosten-Nutzen-Analyse; Mikroökonometrie; USA